Plant Design for the Production of Propylene Oxide by Isopropylbenzene 2-phenylpropane, or (1-Methylethyl) Benzene (Cumene) (American Journal of Innovation in Science and Engineering, 2024)
Cumene is a colorless, volatile liquid with a gasoline-like odor. It’s also known as isopropylbenzene, 2-phenylpropane, or (1-methylethyl) benzene. It’s a natural component of coal tar and crude oil, and it can also be employed in gasoline as a blending component. Cumene hydroperoxide is produced by oxidizing cumene with benzene and propylene in the presence of air. As a result, the cumene hydroperoxide is changed to cumyl alcohol, which is then transformed to propylene without the use of oxygen. Propylene oxide is an organic compound produced through various methods such as the cumene process and the hydroperoxide process. The cumene method is preferred due to its low by-product production and high market value of co-products. The reactive distillation process is a feasible method for producing propylene oxide with high purity and reduced costs. Future work includes optimizing processes, developing new catalysts, and improving efficiency. Propylene oxide has practical applications in the production of polyurethane foams, coatings, adhesives, polyether polyols, and propylene glycols.